STRATIFIKASI SOSIAL DALAM NOVEL GADIS KRETEK KARYA RATIH KUMALA - Sholikhin, Sholikhin (JURNAL PESONA, 2017)
This study aims to know and describe social stratification elements thatÂ  found in the Novelâ Gadis Kretekâ by Ratih Kumala. The study can be a valuable lesson in daily life. This study used qualitative method. The result shows that in Novelâ Gadis Kretekâ by Ratih Kumala discoveredÂ  values, social life in society, and the existence of status dissimilarity from high class to low class that caused social stratificationÂ  system of statusÂ  distinction in society. Classification of social society level viewed from dimension of wealth, power, honorary, and knowledge resulted in economy field competition.